Impact of SARS-CoV-2 Infection during Pregnancy and Perinatal Outcome: Findings from Private Hospitals at Dhaka, Bangladesh - Moni, Sadeka Choudhury; Saha, Joysree; Ahmed, Qumrun Nassa; Jahan, Ismat; Jahan, Mosammad Alpana; Sheela, Farhana Afroze; Mannan, MA; Shahidullah, Mohammod (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Introduction: The pandemic novel corona virus (SARS-CoV- 2) infects pregnant women and affects pregnancy outcome. The perinatal outcome of COVID positive pregnancies attended at private hospitals during the last epidemic peak at Dhaka is unknown. The purpose of the study was to evaluate perinatal outcome among COVID positive and COVID negative pregnant women who delivered in the 2 study hospitals at Dhaka during the last epidemic wave. Methods: This retrospective study was conducted in 2 eminent private medical college& hospitals in Dhaka,namely Popular medical college &hospital (PMCH) and Greenlife medical college hospital (GLMC) over a period of 3 months from July 2021 to September 2021. COVID positive and COVID negative pregnant women who delivered in the study hospitals during the study period were included in this study. Outcome variables were COVID related maternal morbidity mortality, rate of caesarean delivery, stillbirth, preterm birth, low birth weight, neonatal COVID-19 positivity, neonatal death. Results: This study included 60 COVID positive and 60 COVID negative pregnant cases. COVID positive pregnant women delivered at earlier gestational age (weeks) than COVID negative cases(34.46±3.58 vs 36.50±3.20; p=0.001) Among COVID infected pregnancies,severe disease was observed in 15%; O2 support was needed in 68.3% and ICU admission required in 16.7% cases.The caesarean delivery rate ((93.3% vs 80%; p-.032) and preterm delivery rate (63.3% vs 35%; p-.002) were significantly higher among COVID positive cases. About 8.3% COVID affected pregnancies ended up with stillbirth.Maternal death rate due to COVID related complications was 5%.Proportion of low birth weight (LBW) was significantly more in infected pregnancies (65% vs 35%; p 0.001).No newborn from COVID positive mother was tested positive by RT-PCR at 24 hours of age. Conclusion: SARS-CoV-2 infection during pregnancy cancause moderate to severe disease requiring ICU admission and maternal death in 5% among COVID positive cases .It gives rise to more still birth, preterm birth, increasing number of LUCSand LBW. However maternal to neonatal transmission is not evident at 24-hour RT-PCR testing. J Bangladesh Coll Phys Surg 2022; 40: 270-278